2017
DOI: 10.1007/s10461-017-1992-2
|View full text |Cite
|
Sign up to set email alerts
|

High Burden of HIV, Syphilis and HSV-2 and Factors Associated with HIV Infection Among Female Sex Workers in Tanzania: Implications for Early Treatment of HIV and Pre-exposure Prophylaxis (PrEP)

Abstract: This paper estimates population-based prevalence of HIV, syphilis, HSV-2 and factors influencing HIV infection using a national sample of 1914 female sex workers (FSWs) in 7 regions in Tanzania. Additionally, HIV incidence was estimated by comparing biological HIV results with self-reported HIV status. The average HIV prevalence among FSWs in all 7 regions was 28%, ranging from 14% in Tabora to 38% in Shinyanga. HIV incidence was found to be 13 per 100 person-years. Syphilis prevalence was 8% with significantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 34 publications
0
13
1
Order By: Relevance
“…The prevalence of HIV among FBWs (7.1%) was also lower than a recent estimate of HIV prevalence among FSWs in DSM (32%) (Vu and Misra, 2018) .…”
Section: Discussioncontrasting
confidence: 72%
“…The prevalence of HIV among FBWs (7.1%) was also lower than a recent estimate of HIV prevalence among FSWs in DSM (32%) (Vu and Misra, 2018) .…”
Section: Discussioncontrasting
confidence: 72%
“…Evidence shows that in 2014, STI prevalence ranged from 24.9% to 77.5%; between half and two-thirds of FSW have a curable STI at any one time, 30% have reactive syphilis serology and 10% or more have an active genital ulcer [14]. A recent study in Tanzania also found high burden of syphilis (8%) and herpes simplex (HSV) type 2 (60%) [15]. Similar findings have been reported in Ugandan studies that have found high burden of STIs including herpes simplex virus (HSV) type 2 (80%), gonorrhea (13%) and chlamydia (9%) [8, 10].…”
Section: Introductionmentioning
confidence: 99%
“…There is low uptake of STI and HIV screening services among FSW in Uganda; only 53% of FSW had previously tested for HIV in one study [8]. Limited data are available regarding regularity and correlates of STI and HIV screening among FSW in SSA [8, 15, 30].…”
Section: Introductionmentioning
confidence: 99%
“…Viruses are acellular ultra-microscopic metabolically inert obligate intracellular parasites of cellular hosts (Chattopadhyay et al, 2009b), associated with diverse diseases and are threats to human, wildlife, and livestock (Malosh et al, 2017;Marston et al, 2017;Prkno et al, 2017;Akbari and Elmi, 2017;Vu and Misra, 2018). Many are incurable and have no effective antiviral drugs except a very few (forty) US FDA approved antiviral drugs available for the management of some viral diseases.…”
Section: James Lovelockmentioning
confidence: 99%